Effect of Spacing and Corm Size on Growth and Yield of Elephant Foot Yam (Amorphophallus paeoniifolius) Under South Gujarat Conditions - Patel, J.C.; Patel, N.B.; Saravaiya, S.N.; Desai, K.D.; Tekale, G.S. (JOURNAL OF ROOT CROPS, 2013)
No abstract